Aplikasi Monitoring Aquarium untuk Mengurangi Tingkat Kematian dengan Menggunakan Arduino - Kezia Kurniawati; Agustinus Noertjahyana; Handry Khoswanto (Jurnal Infra, 2020)
In the advanced era of globalization, fish care can be created using special system to monitor the aquarium. The system that can be controlled via Android becomes one of the most comfortable to use. By using a microcontroller that is connected to the internet, it can monitor the aquarium using sensors in real time and automatically insert data into the database. Through the Blynk application, fish owners can adjust environmental conditions by entering desired requirements. You can monitor data obtained from sensors through a website that is directly connected to the microcontroller. The test is carried out in 2 different fish environments (no system environment and monitoring system environment). The monitoring system in this study not only can monitors 4 parameters in the aquarium (feeding, water temperature, water level, and water pH) but also controls most of the parameters in the aquarium (except water pH). Based on the results of the study, the monitoring system environment has fish mortality rate of 20% with temperatures around 28 °C while non monitoring system environment has fish mortality rate of 50% with temperatures above 30 °C.